2014
DOI: 10.1007/s13277-014-2833-9
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-lymphocyte ratio acts as a prognostic factor for patients with advanced hepatocellular carcinoma

Abstract: The platelet count, as an inflammation marker, is involved in the progress of tumor invasion. However, the prognostic value of platelet counts and the platelet-to-lymphocyte ratio (PLR) has not been investigated in patients with advanced hepatocellular carcinoma (HCC). This study aimed to determine the prognostic value of platelet counts and PLR in HCC patients. A total of 243 ethnic Chinese advanced HCC patients from two major hospitals, not receiving systemic sorafenib, were analyzed retrospectively. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 26 publications
1
73
1
Order By: Relevance
“…In HCC however, the results were still conflicting regarding the prognostic value of PLR to predict overall survival and the optimal cut-off of PLR remains unclear (11,(17)(18)(19)(20).…”
Section: Original Articlementioning
confidence: 99%
“…In HCC however, the results were still conflicting regarding the prognostic value of PLR to predict overall survival and the optimal cut-off of PLR remains unclear (11,(17)(18)(19)(20).…”
Section: Original Articlementioning
confidence: 99%
“…A recently validated index of systemic inflammation, using the levels of only 2 liver-derived proteins, Creactive protein (CRP) and albumin has been shown in multiple studies to be an independent prognosticator of survival [4][5][6]. The platelet to lymphocyte ratio is another recently described, independent inflammatory prognostic index for HCC [7]. In this paper, we validated the new Aggressiveness Index on a separate and much larger HCC patient cohort in relation to survival and we examined liver function parameters in relation to the index.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, In a recent issue of Tumor Biology, Xing Li and his colleagues published an article [1] entitled BPlatelet-tolymphocyte ratio acts as a prognostic factor for patients with advanced hepatocellular carcinoma.^In this study, the investigators aimed to determine the prognostic value of platelet-to-lymphocyte ratio in a total of 243 advanced hepatocellular carcinoma (HCC) patients from two major hospitals. The investigators concluded that patients with a high platelet-to-lymphocyte ratio (PLR) had a lower 3-month survival rate (37.6 vs. 57.6 %) compared with patients with a low PLR.…”
mentioning
confidence: 99%
“…In the literature, it was shown that valvular heart diseases, acute coronary syndromes, hypertension, end-stage renal diseases, and other diseases may potentially affect the PLR [2][3][4][5][6]. In the study of Xing Li et al [1], patients with previous and/or secondary cancers were excluded, while such as heart diseases which is very common in old people (age 57 (19-86)) were not mentioned. Thus, it would be more relevant if the investigators had mentioned these PLR-affecting factors while evaluating PLR as an independent prognostic factor for advanced HCC patients.…”
mentioning
confidence: 99%